Proceso de atención nutricional en paciente de sexo masculino de 22 años con diagnóstico de esteatosis hepática mayo 2023 -octubre 2023. - Rosero Tinuco, Mariela Carolina (2023)
Hepatic steatosis is the excessive accumulation of fat in the liver. This disease usually occurs more frequently in patients who have obesity. It is one of the diseases with a high prevalence, occurring in 25 to 30%. In 2010 it was the eighth cause of death in Ecuador while in 2011 it was the ninth, being more common in men than in women. This case study is based on a 22-year-old male patient who goes to the hospital with symptoms such as weakness, nausea, and yellowing of the skin. The objective of this clinical case is the nutritional care process in a 22-year-old male patient with a diagnosis of hepatic steatosis, which is based on a 1377 kcal diet. The line of research in this case is health and nutritional well-being. The nutritional status of the patient was assessed, resulting in Type I Obesity; a nutritional plan was developed for the patient that consisted of a 1377 kcal diet. The patient was able to improve his quality of life, this was evidenced by his change in weight and mood.